Chronic Pancreatitis Associated with the p.G208A Variant of PRSS1 Gene in a European Patient - Hegyi, Eszter; Cierna, Iveta; Vavrova, Ludmila; Ilencikova, Denisa; Konecny, Michal; Kovacs, Laszlo (JOP. Journal of the Pancreas, 2014)
Context The major etiologic factor of chronic pancreatitis in adults is excessive alcohol consumption, whereas among children structural anomalies, systemic and metabolic disorders, and genetic factors are prevalent. Mutations in the cationic trypsinogen gene (PRSS1) cause hereditary pancreatitis, while mutations in serine protease inhibitor Kazal type 1 (SPINK1), cystic fibrosis transmembrane conductance regulator (CFTR) and chymotrypsin C (CTRC) genes have been shown to associate with chronic pancreatitis as independent risk factors. Case report We present a case of 13-year-old boy with idiopathic chronic pancreatitis. Given the unexplained attacks of pancreatitis since early childhood and despite the negative family history, molecular-genetic analysis of four pancreatitis susceptibility genes (PRSS1, SPINK1, CTRC and CFTR) was performed. The boy was found to carry the c.623G>C (p.G208A) mutation of the PRSS1 gene and the c.180C>T (p.G60G) mutation of the CTRC gene, both in heterozygous state. These mutations are considered as contributing risk factors for chronic pancreatitis. Conclusions In children with idiopathic chronic pancreatitis genetic causes should be considered, even in absence of positive family history. To the best of our knowledge, this is the first description of a European patient with chronic pancreatitis associated with the p.G208A mutation of PRSS1 gene. This mutation was previously reported only in Asian subjects and is thought to be a unique genetic cause of pancreatitis in Asia. Image: Sequence chromatograms.